Do Ganoderma Species Represent Novel Sources of Phenolic Based Antimicrobial Agents? - Milena Rašeta; Jovana Mišković; Eleonora Čapelja; Ewa Zapora; Aleksandra Petrović Fabijan; Petar Knežević; Maja Karaman (Molecules, 2023)
Ganoderma species have been recognized as potential antimicrobial (AM) agents and have been used in traditional Chinese medicine (TCM) for a long time. The aim of this study is to examine the AM potential of autochthonous Ganoderma species (G. applanatum, G. lucidum, G. pfeifferi and G. resinaceum) from Serbia. The extraction of fungal material was prepared in different solvents (ethanol—EtOH, water—H2O, chloroform—CHCl3). Antibacterial activity (ABA) was determined using disk-diffusion, agar-well diffusion, and micro-dilution method, while for antifungal properties disk-diffusion and pour plate method were applied. Antiviral activity was tested on model DNA virus LK3 and determined by plaque assay. Statistical PCA analysis was applied for detection of correlation effects of phenolics and AM activities, while LC-MS/MS was performed for phenolics quantification. G. resinaceum CHCl3 extract expressed the most potent ABA against P. aeruginosa (MIC = 6.25 mg/mL), probably due to presence of flavonoids and 2,5-dihydroxybenzoic acid. Among H2O extracts, the highest ABA was determined for G. pfeifferi against both E. coli and S. aureus (21 and 19 mm, respectively). EtOH extracts of G. pfeifferi and G. resinaceum were the most effective against A. niger (23.8 and 20.15 mm, respectively), with special impact of phenolic acids and flavonoid isorhamnetin, while C. albicans showed the lowest susceptibility. The most potent antiviral inhibitor was G. lucidum (70.73% growth inhibition) due to the high amount of phenolic acids. To the best of our knowledge, this is the first report of a methodical AM profile of G. pfeifferi and G. resinaceum from the Balkan region including PCA analysis.